Pengaruh Layout dan Citra Merek Terhadap Pengambilan Keputusan Pembelian pada Starbucks Ruko Vienna di Tangerang Selatan - Muhammad Mahdi; Cornelia Dumarya Manik (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - This study aimed to examine the effect of layout and brand image on purchasing decision making among consumers of Starbucks Ruko Vienna, South Tangerang. The research employed a quantitative descriptive method, with data collected through questionnaires using a Likert scale. The sample consisted of 99 respondents selected using purposive sampling. Data analysis was conducted using simple and multiple linear regression, t-tests, and F-tests. The results showed that layout had a positive and significant effect on purchasing decisions, with a significance value of 0.001 < 0.10. Brand image also had a positive and significant effect on purchasing decisions, with a significance value of 0.001 < 0.10. Simultaneously, layout and brand image had a positive and significant effect on purchasing decisions, as indicated by an F value of 127.336 > F table 3.09 and a significance value of 0.001 < 0.10. Therefore, it was concluded that layout and brand image, both partially and simultaneously, had a positive and significant influence on purchasing decisions at Starbucks Ruko Vienna, South Tangerang.